2014
DOI: 10.12659/msm.890137
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Effects of anti-IgE Therapies

Abstract: Source of support:Self financing Omalizumab, a humanized mAb that binds to the CH3 domain near the binding site for the high-affinity type-I IgE Fc receptors of human IgE, can neutralize free IgE and inhibit the IgE allergic pathway without sensitizing mast cells and basophils. We found that omalizumab in patients with severe persistent asthma (SPA) was an effective therapy for asthma and the following co-morbid conditions: chronic urticaria (CU), bee venom allergy, latex allergy, atopic dermatitis, food aller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 86 publications
(92 reference statements)
0
23
0
2
Order By: Relevance
“…Anti-IgE treatment with omalizumab, a well-studied humanized recombinant IgG 1 monoclonal antibody with multiple mechanisms of action beyond binding free IgE [112], is an option in severe asthmatics with confirmed perennial allergies (pets or mites). In patients with severe allergic asthma, the add-on treatment with omalizumab has been shown to reduce the risk of exacerbations [113117], the asthma symptoms [113,114,116,118], and the use of OCS [118] and ICS [115], as well as to improve the quality of life and lung function [113,114,116], without significant safety concerns.…”
Section: Management Of Severe Asthmamentioning
confidence: 99%
“…Anti-IgE treatment with omalizumab, a well-studied humanized recombinant IgG 1 monoclonal antibody with multiple mechanisms of action beyond binding free IgE [112], is an option in severe asthmatics with confirmed perennial allergies (pets or mites). In patients with severe allergic asthma, the add-on treatment with omalizumab has been shown to reduce the risk of exacerbations [113117], the asthma symptoms [113,114,116,118], and the use of OCS [118] and ICS [115], as well as to improve the quality of life and lung function [113,114,116], without significant safety concerns.…”
Section: Management Of Severe Asthmamentioning
confidence: 99%
“…However, such effects require 3-4 weeks to occur, at least on mast cells, which is a far longer time than the few days needed to see the decrease in urticaria severity score. In fact, omalizumab exerts a number of other effects [68], not least on the coagulation pathway where it leads to a marked reduction of D-dimer plasma levels [69] in a way similar to heparin [68]. Notably, some studies have shown the clinical efficacy of anticoagulant therapy in patients with CSU [45][46][47][48]70].…”
Section: Omalizumabmentioning
confidence: 99%
“…Omalizumab interferes with the inflammatory cascade by reducing serum IgE levels and FcɛRI receptor expression on key cells. This results in the inhibition of the release of inflammatory mediators from mast cells and diminished recruitment of inflammatory cells, especially eosinophils, into the airways (1316). …”
Section: Anti-igementioning
confidence: 99%